Framework for field-scale application of molecular biological tools to support natural and enhanced bioremediation - Key, Trent A.; Sorsby, Skyler J.; Wang, Yingnan; Madison, Andrew S. (Frontiers in Microbiology, 2022)
Natural microorganisms present at environmental contaminated sites are capable of biodegrading, biotransforming, or removing contaminants in soil and groundwater through bioremediation processes. Cleanup strategies and goals for site remediation can be effectively achieved by bioremediation leveraging the capabilities of microorganisms to biotransform contaminants into lesser or non-toxic end products; however, reproducible success can be limited by inadequate design or performance monitoring. A group of biological analyses collectively termed Molecular Biological Tools (MBTs) can be used to assess the contaminant-degrading capabilities and activities of microorganisms present in the environment and appropriately implement bioremediation approaches. While successful bioremediation has been demonstrated through previously described lab-scale studies and field-scale implementation for a variety of environmental contaminants, design and performance monitoring of bioremediation has often been limited to inferring biodegradation potential, occurrence, and pathways based on site geochemistry or lab-scale studies. Potential field-scale application of MBTs presents the opportunity to more precisely design and monitor site-specific bioremediation approaches. To promote standardization and successful implementation of bioremediation, a framework for field-scale application of MBTs in a multiple lines of evidence approach is presented. The framework consists of three stages: (i) “Assessment” to evaluate naturally occurring biogeochemical conditions and screen for potential applicability of bioremediation, (ii) “Design” to define site-specific bioremediation approach and inform amendment selection, and (iii) “Performance Monitoring” to generate data to measure or infer bioremediation progress following implementation. This framework is introduced to synthesize the complexities of environmental microbiology and guide field-scale application of MBTs to assess bioremediation potential and inform site decision-making.